Immunisation effect in host following oral exposure to graded doses of immunogenic lipopolysaccharide extracted from Pasteurella multocida type B:2 - Helmy, Sarah (2016)
In Malaysia, Pasteurella multocida serotype B:2 is the causative agent of haemorrhagic septicaemia (HS), a highly fatal disease in buffalo and cattle. Lipopolysaccharide (LPS) is one of the major immunogen of P. multocida. This study aims to determine the protective effect due to oral inoculation of LPS extracted from P. multocida B:2 against HS disease. Twenty-five healthy mice were divided into five groups consisting of five animals each. The control group was inoculated orally with 0.2ml of Phosphate Buffer Saline (PBS) pH 6.8, whereas Group 1, Group 2, Group 3 and Group 4 were inoculated orally with 0.2ml lipopolysaccharides extracted from 103, 105, 107 and 109cfu of Pasteurella multocida serotypes B:2, respectively. The experimental animals were observed for clinical signs for seventeen days. All the groups were subjected for challenge with 0.2 mL of 107 wild type Pasteurella multocida B:2 after 17 days post LPS inoculation. Then, the groups were observed for clinical signs for seven days. After seven days, surviving mice were euthanised and the organs were collected for histopathological examination and bacterial isolation and identification. Before death, 60% of the animals from all group had diarrhoea, 38.5% had severe ocular discharge and 100% had laboured breathing. Mild to moderate histopathological lesions were observed in heart, lungs, liver, spleen, kidney, small intestine, large intestine, small intestine and stomach of all groups. Significantly (P<0.05), Group 1 had mild presence of inflammatory cells in spleen (1.4) and small intestine (0.7), whereas Group 4 had mild to moderate degeneration and necrosis of kidney (1.1) and stomach (2.2). P. multocida was isolated from heart, lung, liver, spleen, kidney and gastrointestinal tract of all groups. Rate of animal mortality showed no significant different (P>0.05) between control group (40% mortality), low concentration group (Group 1 and Group 2) (33.33% mortality) and high concentration group (Group 3 and Group 4) (66.67% mortality). This showed that oral inoculation of LPS extracted from P. multocida, both in low and high concentration, in mice, failed to give immunity to the host.